The Correlation Between The Sitting Posture and Duration With LBP Complaints in Nursing Students During Lecture Activitie - Pattimura, Nadira; Makatita, Sakina; Pattimura, Nastain Abubakar; Tihurua, Ma’syari Arfah (Medicor : Journal of Health Informatics and Health Policy, 2024)
Lower Back Pain (LBP) is a frequently reported issue among people in different domains, including students enrolled in nursing education programmes. Nursing students frequently endure prolonged periods of sitting during their participation in lecture activities. An unergonomic sitting posture and extended periods of sitting can increase the likelihood of experiencing lower back pain (LBP) complaints. This study investigated the correlation between sitting posture and duration and the occurrence of low back pain (LBP) complaints in nursing students at the College of Health Sciences of Pasapua Ambon. This research methodology was characterised by its analytical nature and relies on primary data collected using a cross-sectional approach. A total of 76 participants were included in the study, and they were provided with a Google form including a questionnaire to complete. The acquired data was subsequently examined using both univariate and bivariate methods. The findings indicated no statistically significant correlation between the sitting posture and complaints of lower back pain (LBP). A notable correlation existed between the amount of time spent sitting and lower back pain (LBP) symptoms. These findings suggest that focusing on the amount of time spent sitting rather than the specific sitting posture to reduce lower back pain complaints among university students is more crucial. This highlights the necessity of restricting extended periods of sitting while also emphasising the importance of taking sufficient breaks and engaging in frequent stretching.